Analysis and Design of a Sales Application System for Micro-Scale Grocery Stalls - Darip, Mochammad; Permana, Basuki Rakhim Setya (Journal of Advances in Information and Industrial Technology, 2024)
Investments in information technology often require relatively large capital allocations, but a wise strategy can optimize the use of these funds, such as through developing desktop-based sales applications according to more specific needs and scope. The grocery stall 'CV Warung Berkah' will apply this strategy to manage inventory in sales transactions. The method in designing this sales system uses the waterfall method approach, while finding out the percentage of benefits of the system built with the investment costs incurred using the return-on-investment method approach. Based on the results of the analysis and discussion in the research conducted, the sales system application for micro-scale basic food stalls is feasible to be implemented or developed with an investment feasibility test value or what is usually called ROI of 62.0%. This application system, all sales transactions are recorded accurately as material for the shop owner's analysis in deciding to purchase and inventory goods.